Sistem Penunjang Keputusan Untuk Mengetahui Kerusakan Bangunan Sekolah Menggunakan Metode Fuzzy Logic - Ageng Setiani Rafika; Ignatius Agus Supriyono; Abdu Roqy (UNIVERSITAS RAHARJA, 2021)
The development of technology and information in the era of globalization is growing very rapidly, in addition to being a medium of communication and information, the existence of technology and information also helps humans in completing all work. The world of education in schools is very important in supporting science, therefore the condition of buildings in schools is very important, so this system was created as a solution to be able to solve problems in educational facilities in Indonesia, especially in school buildings with a system of presenting data on the condition of school buildings, after The purpose of the data is to be able to provide information effectively and more efficiently about the condition of the school building so that decisions or actions can be taken on the condition of the school building. The purpose of this system is in addition to being able to provide information on the condition of damage to building components in schools, it is also hoped that it can assist the school in making decisions about buildings in its schools that must be addressed immediately. Because with this system can help provide information to the school to immediately deal with damage to the school building.